Appropriate breeds and breeding schemes for sheep and goats in the tropics - Baker, R.L.; Gray, G.D. (Australian Centre for International Agricultural Research, 2004)
The purpose of this chapter is two-fold. First, the information available on breeds of sheep and goats that are resistant or resilient to helminthiasis (mainly the GI nematodes) infections are reviewed. This is important information for inclusion of appropriate breeds in integrated endoparasite control programs, which may include resistant breeds or genotypes, improved nutrition, strategic drenching, improved management (e.g. housing animals in the wet season) and rotational grazing (Barger 1996, Waller 1997, Alo et al., this volume). However, most of the breeds of sheep and goats that have been identified as resistant or resilient are tropical indigenous ones. Many people, including smallholder farmers in the tropics, often perceive these relatively small indigenous breeds to be unimproved with low genetic potential for increased production. Almost invariably, larger breeds with higher growth rates are assumed to be more productive and often the larger breeds are exotic breeds that are poorly adapted to tropical conditions. Therefore, the second part of this paper discusses how practical breeding programs in the tropics might be developed taking into account both adaptability (disease resistance is just one component of adaptability) and productivity. Particular emphasis is placed on the need to better understand different farming systems in the tropics, their production objectives and the different constraints to increasing productivity before embarking on genetic improvement programs.